Development of consensus-based national antimicrobial stewardship competencies for UK undergraduate healthcare professional education. Issue 3 (November 2018) - Courtenay, M.; Lim, R.; Castro-Sanchez, E.; Deslandes, R.; Hodson, K.; Morris, G.; Reeves, S.; Weiss, M.; Ashiru-Oredope, D.; Bain, H.; Black, A.; Bosanquet, J.; et al.
Summary: Background: Healthcare professionals are involved in an array of patient- and medicine-related stewardship activities, for which an understanding and engagement with antimicrobial stewardship (AMS) is important. Undergraduate education provides an ideal opportunity to prepare healthcare professionals for these roles and activities. Aim: To provide UK national consensus on a common set of antimicrobial stewardship competencies appropriate for undergraduate healthcare professional education. Methods: A modified Delphi approach comprising two online surveys delivered to a UK national panel of 21 individuals reflecting expertise in prescribing and medicines management with regards to the education and practice of nurses and midwives, pharmacists, physiotherapists, and podiatrists; and antimicrobial prescribing and stewardship. Data collection took place between October and December 2017. Findings: A total of 21 participants agreed to become members of the expert panel, of whom 19 (90%) completed round 1 questionnaire, and 17 (89%) completed round 2. Panelists reached a consensus, with consistently high levels of agreement reached, on six overarching competency statements (subdivided into six domains), and 54 individual descriptors essential for antimicrobial stewardship by healthcare professionals. Conclusion: Due to the consistently high levels of agreement reached on competency statements and their associated descriptors, this competency framework should be used to direct education for undergraduate healthcare professionals, and those working in new clinical roles to support healthcare delivery where an understanding of, and engagement with, AMS is important. Although the competencies target basic education, they can also be used for continuing education.